On the radiation phase stability of a relativistic coaxial backward-wave oscillator at decimeter wavelengths; Technical Physics Letters; Vol. 41, iss. 1 - Totmeninov E. M. Evgeny Markovich; Klimov A. I. Aleksey Ivanovich; Konev V. Yu. Vladimir Yurievich; Rostov V. V. Vladislav Vladimirovich; Stepchenko A. S. Alexei Stanislavovich; Tsygankov R. V. Ruslan Vyacheslavovich (2015, 2015)
Title screen